Keterkaitan antara Karakter Religius dan Literasi Sains pada Siswa Sekolah Dasar - Wulandari, Ratna Wahyu; Rahmawati, Novi Rosita (FONDATIA, 2025)
Education in Indonesia faces the challenge of integrating the development of spiritual character with scientific cognitive abilities, which have often been treated as separate domains. This study aims to examine the relationship between religious character and scientific literacy among elementary school students. A quantitative approach with a correlational design was employed. The sample consisted of 120 fifth- and sixth-grade students at SDI Plus Hidayatut Tholibin, selected through purposive sampling. Data were collected using a religious character questionnaire and a scientific literacy test, then analyzed descriptively and through Pearson correlation. The results show that students’ religious character falls into the "good" category, while their scientific literacy is in the "adequate" category. Correlation analysis revealed a significant positive relationship between religious character and scientific literacy (r = 0.554; p < 0.05). These findings indicate that both aspects can mutually reinforce each other within the educational process. The study concludes that integrating religious character education with science education can foster students with a strong moral foundation and critical scientific thinking skills, offering implications for the development of integrated curricula in primary education.